PENGARUH SOSIAL MEDIA, PERSEPSI HARGA DAN GAYA HIDUP TERHADAP LOYALITAS KONSUMEN PRODUK KOPI DI POINT COFFEE INDOMARET KIRONGGO PALEMBANG - Sari, Tiara Dwi Novita; Helmi, Muhamad; Hendrayani, Iin; Jannah, Miftahul (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The more coffee shops there are, the more competition there is, which requires producers to be more aggressive in retaining consumers so that they make repeat purchases and become loyal consumers. Factors that influence consumer loyalty are social media, price perception, and lifestyle. Thisostudyoisoto assesses the impact of social media, price perception, and lifestyle both individually and together on consumer loyalty towards coffee products at Point Coffee Indomaret Kironggo Palembang. The locus of this research is Point Coffee Indomaret Kironggo Palembang, located at 30 Ilir, Ilir Barat II District Palembang. This study employs quantitative research utilizing descriptive and verification analytic methodologies. The sampling technique used accidental techniques with a total sample of 100 respondents obtained through the distribution of questionnaires. This study indicates that social media characteristics, price perception, and lifestyle partially influence consumer loyalty. The study concludes that the independent variables (social media, price perception, and lifestyle) jointly influence the dependent variable (consumer loyalty) at Point Coffee Indomaret Kironggo Palembang.